Element Extraction in Packaging Design of Cireng Rujak X with Kansei Engineering Method - Sari, Novi Purnama; Indriany, Dita Febrian; Yunisyah, Fadilah; Wiguna, Nada Nabilla (Jurnal Teknologi, 2025)
Frozen Cireng Rujak is popular for its practicality, but the packaging of Cireng Rujak X still has many shortcomings that affect its quality. These issues arise from packaging that cannot be resealed and labels that are easily damaged. This research aims to determine the elements and design outcomes of Cireng Rujak X packaging based on consumer preferences. The study employs the Kansei Engineering method to understand consumer perceptions of the packaging. This method is supported by Quantification Theory Type-1 (QTT-1) to identify design elements. The selected concept based on QTT-1 is "Unprotection-Simple" with a score of 0.921. The resulting design elements include No Lid (X1.7), Flat Bottom shape (X2.8), Ziplock feature (X3.2), Aluminum Foil material (X4.8), Large volume (X5.3), Minimalist design style (X6.2), surface design using Labels or Stickers (X7.2), and Informative label design (X8.1). The mock-up design based on the selected concept aligns with consumers' emotional preferences.